A case of an 11-year-old girl diagnosed with OCD developing giggle incontinence following addition of aripiprazole to treatment. Issue 3 (3rd July 2018) - Akaltun, İsmail; Kara, Tayfun; Ayaydın, Hamza
ABSTRACT: Giggle incontinence (GI) is characterized by involuntary and generally unpredictable release of urine during giggling or laughter. It has been suggested that GI may be a centrally mediated disorder and may share a common pathophysiology with narcolepsy and cataplexy. The fact that methylphenidate reduces some symptoms suggests that the condition may be a cataplexy. While alpha 1 and dopamine D2 antagonists exacerbate cataplexy, alpha 1 and dopamine D2 agonists produce a marked improvement. Aripiprazole, frequently used to augment treatment of obsessive compulsive disorder, may have exhibited an alpha 1 and D2 receptor antagonist effect and have caused GI. We describe a case of GI occurring following aripiprazole use in an 11-year-old female obsessive compulsive disorder patient resistant to treatment.